Altered Maturation Status and Possible Immune Exhaustion of CD8 T Lymphocytes in the Peripheral Blood of Patients Presenting With Acute Coronary Syndromes. Issue 2 (February 2016) - Zidar, David A.; Mudd, Joseph C.; Juchnowski, Steven; Lopes, Joao P.; Sparks, Sara; Park, Samantha S.; Ishikawa, Masakazu; Osborne, Robyn; Washam, Jeffrey B.; Chan, Cliburn; Funderburg, Nicholas T.; Owoyele, Adeyinka; et al.
Abstract : Objective—: Inflammation in response to oxidized lipoproteins is thought to play a key role in acute coronary syndromes (ACS), but the pattern of immune activation has not been fully characterized. We sought to perform detailed phenotypic and functional analysis of CD8 T lymphocytes from patients presenting with ACS to determine activation patterns and potential immunologic correlates of ACS. Approach and Results—: We used polychromatic flow cytometry to analyze the cytokine production profiles of naïve, effector, and memory CD8 T cells in patients with ACS compared with control subjects with stable coronary artery disease. ACS was associated with an altered distribution of circulating CD8 + T-cell maturation subsets with reduced proportions of naïve cells and expansion of effector memory cells. ACS was also accompanied by impaired interleukin-2 production by phenotypically naïve CD8 T cells. These results were validated in a second replication cohort. Naïve CD8 cells from patients with ACS also had increased expression of programmed cell death-1, which correlated with interleukin-2 hypoproduction. In vitro, stimulation of CD8 T cells with oxidized low-density lipoprotein was sufficient to cause programmed cell death-1 upregulation and diminished interleukin-2 production by naïve CD8 T cells. Conclusions—: In this exploratory analysis, naïve CD8 + T cells from patients with ACS show phenotypic and functional characteristics of immune exhaustion: impaired interleukin-2 production and programmed cell death-1 upregulation. Exposure to oxidized low-density lipoprotein recapitulates these features in vitro. These data provide evidence that oxidized low-density lipoprotein could play a role in immune exhaustion, and this immunophenotype may be a biomarker for ACS. Abstract : Supplemental Digital Content is available in the text.